The effectiveness of promotionals tools towards customer awareness for Biossentials Puri Spa, Melaka / Ielda Suraya Yahaya - Yahaya, Ielda Suraya (Faculty of Business and Management, 2009)
Biossentials Puri Spa was opened in March 2006. Such as new company Biossentials Puri Spa need to make effective promotion in order to create awareness to the customer beside most of the customer unaware the existing of Bioassential Puri Spa Due to that problem matter, researcher does the research study on the effectiveness of promotional tools in enhancing customer awareness of Biossential Puri Spa that come with the objectives,(i) to study the effectiveness of existing promotion tools used by Biossentials Puri Spa, (ii) to identify which promotional tools are the effective to increase customer awareness and (iii) to determine the level of customer awareness toward promotional activity of Biossentials Puri Spa. In this study, the research design of Descriptive Research and Causal Research are being used. For sampling technique, researcher used Simple Random Sampling in non.. probability for this study. Researcher distributed the sixty questionnaires to respondents randomly around Melaka Tengah to have primary data for data analysis and other sources of secondary data from reports journals and so on. Once the necessary data has been collected, the data will be analyzed and summarized in a readable and easily interpretable form. The Statistical Package for the Special Science (SPSS) has been used to summarize data. The results are in the form of reliability testing, frequency, percentage, mean and rank. This research found that respondents are still unaware with the existing Biossentials Puri Spa. So they need choose the effectiveness promotional tools in enhancing customer awareness and in order to boost the sales.